Direct ex vivo measurement of CD8(+) T-lymphocyte responses to human parvovirus B19. - Tolfvenstam, T; Oxenius, A; Price, D; Shacklett, B; Spiegel, H; Hedman, K; Norbeck, O; Levi, M; Olsen, K; Kantzanou, M; Nixon, D; Broliden, K; et al. (2001)
Parvovirus B19 is a common human pathogen which can cause severe syndromes, including aplastic anemia and fetal hydrops. The mapping of the first parvovirus B19-derived CD8(+) T-lymphocyte epitope is described. This HLA-B35-restricted peptide derives from the nonstructural (NS1) protein and is strongly immunogenic in B19 virus-seropositive donors.